دور منهج في التربية البدنية و الرياضية في تنمية قيم المواطنة لدى تلاميذ الطور المتوسط دراسة ميدانية لتلاميذ الطور المتوسط بمدينة الاغواط - قنيول, بدر الدين; منصوري, نبيل (جامعة البويرة, 2017)
تهدف هذه الدراسة التي بين أيدنا إلى معرفة مدى تأثير مناهج التربية البدنية والرياضية في تعزيز قم المواطنة لدى التلاميذ، وذلك من خلال مجموعة من التدابير والافكار المتضمنة في المنهج التي تعمل كلها من أجل تحقيق مختلف السلوكات والافكار التي تعزز هذه القيم. وتأتي المناهج من العناصر والأدوات الرئيسة التي تستخدمها النظم التربوية لمساعدة أبنائها على تطوير طاقاتهم لأقصى مدى ممكن ليكونوا مواطنين صالحين في المجتمع ، منتجين ومساهمين مسؤولين ومهتمين بشؤون مجتمعهم وقضاياه وحاجاته وهمومه وأولوياته، ومحافظون على نسيجه ويصونون هويته ويبرزونها، ويُفترض أن تكون المنـــاهج التربويــة هي المجال الأساس والقوة الموجهة لتحقيق هذه الأهداف النوعيــة؛ بحيث تبني المتعلمين بشكل تكاملي شمولي بنــائي يواكب أحدث التطورات والمستجدات العالمية. الكلمات الدالة: منهاج التربية البدنية و الرياضية، قيم المواطنة، تلاميذ الطور المتوسط The rol of the curriculum in sports in the developement of values of citizenship among pupils ovrage plase . The world is witnessing now economic ، social and cultural changes that led to the emergence of trends and behaviors which affected negativelyon community cohesionthis generates a feeling among peaple on the existence of threats to their values ، traditions and nationalidentity . these changes impose their effects on various areas of life such as education. That rapid changes require from societies and its educational systems a preparation of human strenghts and students to raise their scientific level ،skills and performance by possessing the knowledge besides proficiency waysof thinking and how to exercise them in addition to the understanding of patrimony and pride of the historical heritage and mastering the languagethen from there stratingto local and international competions. The curriculum comes from the elements and the main tools used by educational systems to help their children to develop their energy to the greatestextent possible to be good citizensproducers and interested in the affairs of their community and its needs and concerns. It is supposed that the educational curriculum is the foundation area and the guiding force to achieve this quality goals so that struturing learners in integrative ،holistic and constructional way that keep pace with thelatest neuoness and international developments
Keywords: منهاج التربية البدنية; قيم المواطنة،